Composition and Distribution of Deep Water Macroalgae Species from the Continental Shelf of Sergipe State, Brazil - Pereira, Sonia Maria Barreto; Torres, Juliana; Gestinari, Lisia Monica De Souza (Phytotaxa, 2014)
This study investigates the deep-water flora of the continental shelf in Sergipe State, Brazil located between 10º36’08’’ – 11º21’07’’S and 36º28’10’’ – 37º13’47’’W. The samples were collected by dragging at 18 sampling sites, between 10 to 30 m depth, from May 1999 to March 2000. A total of 91 taxa of marine benthic macroalgae were identified (56 Rhodophyta, 20 Heterokontophyta and 15 Chlorophyta). Forty-seven (47) of these are new occurrences for Sergipe flora. Rhodophyta dominated, accounting for 61% of the total species collected, with the order Ceramiales having the highest number of species present (39.55%), followed by Heterokontophyta (23%), mostly represented by Dictyotales (65%). Finally, 15 Chlorophyta taxa were found (16%), mainly composed of Bryopsidales (53%).